Chronic stress, executive functioning, and real‐life self‐control: An experience sampling study. Issue 3 (3rd September 2020) - Wolff, Max; Enge, Sören; Kräplin, Anja; Krönke, Klaus‐Martin; Bühringer, Gerhard; Smolka, Michael N.; Goschke, Thomas
Abstract: Objective: To test the hypothesis that chronic stress impairs the use of cognitive control for self‐control, we examined how chronic stress affects the relation between individual differences in general executive functioning (GEF) and self‐control in real‐life situations. Method: About 338 young adults with varying degrees of chronic stress underwent experience sampling of real‐life self‐control for 7 days and completed a battery of nine executive function tasks from which a latent variable representing individual differences in GEF was derived. Results: Structural equation models showed that higher levels of chronic stress were associated with stronger desires and a less negative relationship between GEF and desire strength. Chronic stress and GEF did not predict desire enactment in situations where effortful resistance was attempted. Conclusions: These findings suggest that chronic stress may impair self‐control by reducing the use of cognitive control for "early" desire regulation strategies while leaving "late" resistance strategies unaffected. That relationships between executive functioning and real‐life self‐control can be moderated by third factors such as chronic stress may to some extent explain the common finding of weak or missing associations between laboratory measures of executive functioning and real‐life self‐control.